Comparison of swimming versus running maximal aerobic capacity in helicopter rescue paramedics. Issue 10 (3rd October 2021) - Meadley, Ben; Horton, Ella; Pyne, David B.; Perraton, Luke; Smith, Karen; Bowles, Kelly-Ann; Caldwell, Joanne
Abstract: Swimming is a critical task for helicopter rescue paramedics and aerobic capacity is assessed in this occupation to determine job suitability. We evaluated one treadmill-based and one pool-based assessment of maximal aerobic capacity (V̇O2peak ) in 14 helicopter rescue paramedics. There was a small absolute difference ( p  = 0.11, d  = 0.46) between V̇O2peak in the swim (45.5 ± 7.8 ml.kg −1 .min −1 ) compared to the run (48.5 ± 5.5 ml.kg −1 .min −1 ), with a moderate relationship noted ( r  = 0.74, 95% CI [0.35–, 0.91], p  = 0.0023). Whilst not interchangeable, run V̇O2peak was a predictor of swim V̇O2peak . Maximal blood lactate was similar ( p  = 0.93) in swim (13.4 ± 3.8 mmol.L −1 ) and run (12.2 ± 3.0 mmol.L −1 ), and maximal heart rate 13% lower ( p  < 0.0001) in the swim (162 ± 11 bpm) versus the run (186 ± 10 bpm). To estimate swimming V̇O2peak in paramedics a treadmill test is sufficient but does not replace assessment of swimming proficiency. Practitioner Summary : We developed a swim protocol to assess maximal aerobic capacity in helicopter rescue paramedics. Compared to a treadmill-based test, our swim protocol generated 20% lower submaximal V̇O2 and 6% lower V̇O2peak . Although not interchangeable, a treadmill V̇O2peak test is indicative of maximal aerobic capacity in rescue paramedics whilst swimming. Abbreviations: HEMS: helicopter emergency medical service; PES: physical employment standards; ICFP: intensive care flight paramedic; RPE: rating of perceived exertion